ANALISIS KOMPETENSI ABSOLUT PERKARA PERCERAIAN PERALIHAN AGAMA (STUDI PUTUSAN NOMOR 2/PDT.G/2015/PN SNT): Absolute Competency Analysis Of The Case Divorce Transfer Of Religion (Study Decision Number 2/Pdt.G/2015/Pn Snt) - Karin Marcheni; Gandes Candra Kirana (Faculty of Law, Universitas Trisakti, 2025)
Over time, not all marriages remain harmonious, and the bond of marriage can encounter various issues that may lead to its dissolution through divorce. One such issue is the conversion of religion by one of the spouses. Identification problem of this research the regulations regarding the absolute competence in divorce cases due to religious conversion in Indonesia and to assess whether the judge's decision in case Number 2/Pdt.G/2015/PN Snt aligns with the applicable laws and regulations. The research employs a normative juridical method by analyzing secondary data. This descriptive study outlines the regulations related to the resolution of divorce cases due to religious conversion and analyzes the judge's decision in case Number 02/Pdt.G/2015/PN Snt to ensure its compliance with existing laws. The research result and conclusion; based on Jurisprudence of the Supreme Court Decision Number 726 K/Sip/1976, the District Court has the authority to adjudicate this case, as the applicable law in resolving divorce disputes due to religious conversion is based on the law in effect at the time of marriage. The District Court retains the authority to examine, adjudicate, and decide divorce cases involving religious conversion, even if the plaintiff is a Muslim.